2005
DOI: 10.1111/j.1540-8159.2005.00005.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Resynchronization Therapy:

Abstract: In patients with heart failure and wide QRS complex, cardiac resynchronization therapy (CRT) is associated with improvement of symptoms and cardiac function. This study examined the effects of a 3-month period of CRT on left ventricular (LV) and right ventricular (RV) ejection fraction (EF) and on LV volumes, both at rest and during exercise. A CRT system was implanted in 15 patients with severe heart failure and wide QRS. Before implant and 3 months later, all patients underwent assessment of cardiac performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 19 publications
3
18
0
1
Order By: Relevance
“…We identified seventeen studies, which reported parameters of baseline RV function and LVEF (Figure 1) [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. One study was not included in the final analysis, as it did not provide data in terms of absolute number (and standard deviation) for baseline RV function parameters and LVEF before and after CRT [19].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We identified seventeen studies, which reported parameters of baseline RV function and LVEF (Figure 1) [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. One study was not included in the final analysis, as it did not provide data in terms of absolute number (and standard deviation) for baseline RV function parameters and LVEF before and after CRT [19].…”
Section: Resultsmentioning
confidence: 99%
“…One study was not included in the final analysis, as it did not provide data in terms of absolute number (and standard deviation) for baseline RV function parameters and LVEF before and after CRT [19]. Sixteen studies were selected for final analysis [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Details of the studies and baseline characteristics are summarized in Table 1 Previous studies have reported conflicting effects of baseline RV function on response to CRT.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In einer Vielzahl von kleineren Studien und im CRT-Arm der MIRACLE-Studie konnte nun bereits gezeigt werden, dass CRT zu einem «reversen linksventrikulĂ€ren remodeling» mit Verkleinerung der enddiastolischen und endsystolischen Volumina und Diameter und damit auch zu einer Reduktion der Mitralinsuffizienz fĂŒhrt [9][10][11][12][13]. Bei nĂ€herer Betrachtung der Überlebenskurven aus der COMPANION-Studie wird ersichtlich, dass sich der Vorteil der CRT-Gruppe gegenĂŒber der medikamentös therapierten Gruppe erst nach ungefĂ€hr 8 Monaten herauskristallisiert.…”
Section: Days After Randomizationunclassified